Ecological resistance to Acer negundo invasion in a European riparian forest: relative importance of environmental and biotic drivers. Issue 2 (10th August 2012) - Saccone, Patrick; Girel, Jacky; Pages, Jean‐Philippe; Brun, Jean‐Jacques; Michalet, Richard; Prober, Suzanne
Abstract Question The relative importance of environmental vs. biotic resistance of recipient ecological communities remains poorly understood in invasion ecology. Acer negundo, a North American tree, has widely invaded riparian forests throughout Europe at the ecotone between early‐ (Salix spp. and Populus spp.) and late‐successional (Fraxinus spp.) species. However, it is not present in the upper part of the Rhône River, where native Alnus incana occurs at an intermediate position along the successional riparian gradient. Is this absence of the invasive tree due to environmental or biotic resistance of the recipient communities, and in particular due to the presence of Alnus? Location Upper Rhône River, France. Methods We undertook a transplant experiment in an Alnus‐dominated community along the Upper Rhône River, where we compared Acer negundo survival and growth, with and without biotic interactions (tree and herb layer effects), to those of four native tree species from differing successional positions in the Upper Rhône communities (P. alba, S. alba, F. excelsior and Alnus incana). Results Without biotic interactions Acer negundo performed similarly to native species, suggesting that the Upper Rhône floodplain is not protected from Acer invasion by a simple abiotic barrier. In contrast, this species performed less well than F. excelsior and Alnus incana in environments with intact tree and/or herb layers. Alnus showed the best growth rate in these conditions, indicating biotic resistance of the native plant community. Conclusions We did not find evidence for an abiotic barrier to Acer negundo invasion of the Upper Rhône River floodplain communities, but our results suggest a biotic resistance. In particular, we demonstrated that (i) additive competitive effects of the tree and herb layer led to Acer negundo suppression and (ii) Alnus incana grew more rapidly than Acer negundo in this intermediate successional niche.